Seismic volcanostratigraphy and tectono-magmatic reconstruction of the Jan Mayen microcontinent and Iceland Plateau Rift system - Blischke, Anett (Zenodo, 2021)
This data is part of a G3 manuscript submission as supplement material for the study of the Cenozoic evolution of the Jan Mayen microcontinent - Iceland Plateau Rift (JMMC-IPR) region has revealed a protracted history of continental breakup in the Northeast Atlantic that continues to present day. Focusing on the geodynamic development of the JMMC and the IPR in a dual-breakup setting has provided new constraints on the regional and sub-regional pattern of continental breakup as a response to long-lived tectono-magmatic and Iceland plume - rift interactions by means of a propagating rift system with associated processes of tectonism, sedimentation and volcanism. These observations have substantially enhanced our knowledge regarding non-uniform formation of tectono-magmatic rifted margins and domains. Enabling us to describe the initiation and evolution of the IPR propagated rifting domain that inter-fingers with the southern ridges of the JMMC. This dual breakup scenario and its association to a series of volcanic zones with links to transfer system has been described and the igneous domains of the JMMC-IPR with intrusive and extrusive activities, and regionally extensive flood basalts have been delineated.